Microhardness and Dynamic Yield Strength of Copper Samples upon Impact on a Rigid Wall - N. V. Pakhnutova; E. N. Boyangin; O. A. Shkoda; S. A. Zelepugin (Advanced Engineering Research)
Introduction. One of the commonly used methods for assessing the dynamic characteristics of a material is the Taylor test, which establishes the relationship between the dynamic yield strength of a cylindrical sample material and its length after hitting a non-deformable barrier. The purpose of this work was to study the microhardness and determine the dynamic yield strength of copper samples for various impact velocities in the Taylor test.Materials and Methods. Experiments were carried out with cylindrical copper (M1) samples. The throwing conditions were selected on the ballistic stand, which provided the speed of the sample in the range of 150–450 m/s at the exit from the barrel. After the impact, the microhardness of the samples in the section plane was measured. The calculation of the dynamic yield strength was carried out according to the classical Taylor formula.Results. Experimental data are presented for cylindrical copper samples upon impact on a rigid wall with velocities in the range of 162–416 m/s, including configurations and sizes of images before and after impact. Microhardness distributions in the axial section of the samples were obtained. For each sample, the dependences of the averaged values of microhardness were constructed, which made it possible to identify four areas of deformation of the samples (the area of elastic deformations, plastic deformations, intense plastic deformations, the area of the material undergoing destruction) and determine their sizes. The dynamic yield strength of copper in the studied range of impact velocities was calculated.Discussion and Conclusions. The values of microhardness in the entire considered region and for all studied impact velocities exceeded the initial value. There was a significant increase in the value of the dynamic yield strength compared to its static value. The correlation of the maximum averaged values of microhardness and dynamic yield strength, which grew with increasing impact velocity, was identified.